Optimalisasi Daya Ingat Anak Melalui Permainan Puzzle: Studi Eksperimen - Stacya A, Oey Michelle; Amaliyah, Shofwatun (Innovative: Journal Of Social Science Research, 2025)
The observation that children's memorization abilities are still quite low when playing games is the driving force for this research. This study takes the form of descriptive action research in the classroom. One educator and ten students participated in the study. Research and data analysis have shown that: 1) The teacher's lesson plan for enhancing the memory skills of 5- and 6-year-olds at Fatima Kindergarten Semarang through the use of puzzle games is of a "very good" quality. 2) Children at Fatima Kindergarten Semarang, who are five or six years old, have shown "very good" improvement in their memory skills through the use of puzzle games in the classroom. 3. Children's memory skills can be described as "very well developed" by 70% to 80% after playing puzzle games. Some of the activities included in these games include: remembering objects from puzzle pieces, sorting puzzle pieces to form patterns, and remembering empty images in puzzles. Educators should be able to devise effective strategies for engaging students in learning, with a focus on enhancing the memorization abilities of students in the 5–6 age range through the use of puzzle games.